2020
DOI: 10.1177/0954405420918475
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electrostatic solid lubricant spray process parameters during turning Ti-6Al-4V alloy

Abstract: Titanium alloys are considered as hard-to-cut material due to its relatively high resistance to corrosion, low thermal conductivity and high chemical reactivity. Effective penetration of sufficient amount of lubricant in the metalworking process is of utmost importance to (a) reduce frictional resistance at the high-temperature tool–workpiece interface and (b) avert the formation of built-up edge in machining process. Traditionally, the lubricant forms a thin fluid film to reduce the friction. In order to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The sinusoidal texture gave the best result compared to other tools. Gunda et al [56] optimized the machining parameters using the electrostatically charged lubricant spray technique in the turning of Ti-6Al-4V. The cutting force and surface roughness were notably affected by the higher velocity and number of droplets of the charge lubricants.…”
Section: Wet Machining Strategymentioning
confidence: 99%
“…The sinusoidal texture gave the best result compared to other tools. Gunda et al [56] optimized the machining parameters using the electrostatically charged lubricant spray technique in the turning of Ti-6Al-4V. The cutting force and surface roughness were notably affected by the higher velocity and number of droplets of the charge lubricants.…”
Section: Wet Machining Strategymentioning
confidence: 99%
“…They turned Ti-6Al-4V and reported that this method efficiently provide solid lubricants and that a large number of droplets and a high spaying speed significantly affected the surface roughness. 60 In addition, the appropriate lubrication for machining is crucial to control the chip-tool-workpiece interface. Gunda et al established an experiment setup to provide high-speed minimum-quantity solid lubricant, and investigated MoS 2 lubricants for turning of Ti-6Al-4V and EN31 alloys.…”
Section: Surface Roughness Of Precision-machined Advanced Engineering Materialsmentioning
confidence: 99%
“…Turning is the most basic, most common and most extensive technical method in the mechanical manufacturing industry, which occupies a very important position in production. 58 Extensive use of turning leads many scientific research institutions and production and processing departments to carry on in-depth study on it, meanwhile the development of UAT is also promoted. UAT is different from traditional turning process, which changes from continuous cutting mode of conventional turning (CT) to interrupted cutting and is a typical composite machining method combining ultrasonic vibration with CT. 912…”
Section: Introductionmentioning
confidence: 99%